2021
DOI: 10.1177/1120672121991358
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for scleral fixation using Carlevale lens

Abstract: Purpose: To evaluate the surgical outcomes and feasibility of a novel approach for scleral-fixation using a single-piece acrylic foldable Carlevale lens (Soleko). Methods: Eighteen eyes of 18 patients with aphakia, dislocated IOL, subluxated lens, anisometropia, perforated trauma, and retinal detachment who underwent IOL implantation with a Carlevale lens were evaluated. All the patients underwent a standard ophthalmologic examination. Anterior segment (AS)-OCT was used postoperatively to check plugs positioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 36 publications
2
45
1
Order By: Relevance
“…In our study, the visual outcomes in the iris claw group (group 1) were comparable with the STSPFL group (group 2) both in the overall cohort of patients and in the subgroup without comorbidities (p = 0.15 and p = 0.08, respectively). Our results are consistent with other studies in the literature reporting the early efficacy of the two surgical techniques [12,13]. Indeed, Barca et al [14] reported similar mean post-operative visual outcomes (0.13 ± 12 logMar) and refractive errors (0.71 ± 1.21) at 8 months of follow up in patients who underwent STSPFL implantation, also reporting the great stability of the lens without cases of IOL dislocation and pseudophacodonesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the visual outcomes in the iris claw group (group 1) were comparable with the STSPFL group (group 2) both in the overall cohort of patients and in the subgroup without comorbidities (p = 0.15 and p = 0.08, respectively). Our results are consistent with other studies in the literature reporting the early efficacy of the two surgical techniques [12,13]. Indeed, Barca et al [14] reported similar mean post-operative visual outcomes (0.13 ± 12 logMar) and refractive errors (0.71 ± 1.21) at 8 months of follow up in patients who underwent STSPFL implantation, also reporting the great stability of the lens without cases of IOL dislocation and pseudophacodonesis.…”
Section: Discussionsupporting
confidence: 92%
“…The use of a PCIOL offers many advantages: it takes place near the original lens position; it is distant from corneal endothelium and angle structures; it provides a good mechanical barrier between the vitreous cavity and anterior chamber [1]. Among the PCIOLs, the iris claw lens is universally considered as a very reliable surgical option, while very recently, the use of sutureless trans-scleral plugs fixated lenses is spreading among surgeons [12,13]. In our study, the visual outcomes in the iris claw group (group 1) were comparable with the STSPFL group (group 2) both in the overall cohort of patients and in the subgroup without comorbidities (p = 0.15 and p = 0.08, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In all surgeries, soft dislocated IOL were cut into 2 pieces and removed through a sclero-corneal tunnel enlarged up to 3.0-mm. When a rigid IOL had to be removed, a wider peritomy was performed and IOL itself was extracted through a curvilinear partial-thickness scleral incision as previously reported [10,13,14] …”
Section: Methodsmentioning
confidence: 99%
“…The first technique (group 1) has been previously described. [10] A conjunctival peritomy was performed nasally and temporally and a crescent blade was used to perform 2 opposite straight incisions running posteriorly to the limbus for 2.5 mm at 0°and 180°axis (Fig. 2A).…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation